Characterization of mineral particles in the ice core of the Ushkovsky volcano - A. G. Khairedinova; M. M. Vinogradova; M. A. Vorobyev; S. S. Kutuzov; Yu. N. Chizhova; S. V. Zakusin; V. N. Mikhalenko (Лëд и снег, 2025)
The article presents the investigation of mineral particles from an ice core obtained from Ushkovsky volcano (Kamchatka) in the fall of 2022. The 14-meter-long ice core was studied to identify the causes of mineral dust concentration variability and to determine its sources. Insoluble solid particles, including volcanic ash and mineral dust, were analyzed using stereomicroscopy and X-ray diffraction. Minimum and maximum dust concentration values were 356.4 ppb and 45 969 ppb, respectively, with an average dust mass concentration across all data at 5 099 ppb and a median of 2 784 ppb. The results show a cyclic particle distribution linked to seasonality, with notable concentration peaks likely associated with volcanic activity and the transport of mineral dust from arid regions. It was found that surface melting leads to the leaching of calcium and magnesium ions from layers containing insoluble particles. The displacement of cation peaks relative to dust concentration peaks is variable and likely depends on the meteorological characteristics of individual summer seasons. Mineralogical analysis of the samples shows the presence of plagioclase, as well as clay and ferromagnesial silicates and amorphous silica. Plagioclase dominates at all depths, indicating a predominance of volcanic ashes in the composition of insoluble impurities. The ratio of non-clay minerals (pyroxenes, amphiboles, and amorphous silica) can be used as markers of local transport, while the presence of clay minerals (smectite, kaolinite, chlorite) is suggested as an indicator of long-range transport. Thus, Kamchatka ice cores can be used to study the processes of mineral particle transport in the atmosphere, provided a comprehensive approach is applied, including mineral composition and chemical composition analyses as well as isotopic methods to determine material origin.